Electron energization and transport in the magnetotail during substorms. Issue 2 (22nd February 2014) - Pan, Qingjiang; Ashour‐Abdalla, Maha; Walker, Raymond J.; El‐Alaoui, Mostafa
Abstract It has been suggested recently that electrons are accelerated both near the reconnection site and during subsequent earthward transport. We provide global and quantitative evidence for this two‐step process by examining electron energization during a substorm event that occurred on 11 March 2008, when the Earth's magnetosphere was immersed in southward interplanetary magnetic field and high‐speed solar wind. The approach is to integrate coordinated measurements by Time History of Events and Macroscale Interactions during Substorms (THEMIS), global magnetohydrodynamic (MHD) modeling of the magnetosphere driven by upstream solar wind conditions, and large‐scale kinetics (LSK) simulation. In this event, THEMIS P2 at XGSM ~ − 15 RE detected a dipolarization pulse‐like magnetic structure coupled with energetic electron flux increase. About 1 min later, P3 and P4 at GSM EX ~ − 10 RE observed dipolarized magnetic field and even larger flux increase. These multipoint data are applied to benchmark the MHD/LSK simulation. We quantify electron energization near the reconnection site and during earthward transport. We show that electrons were initially energized near the reconnection site, and subsequently further adiabatically accelerated far away from the reconnection site as the dipolarization front formed and grew. The adiabatic enhancement was rather effective given steep source electron distribution as a function of energy. In the outer magnetosphere with strong flows, E × B drift statistically dominated electron guiding center motion; thus, electrons were transported along the flow channel with small spatial diffusion. Close to the Earth, gradient and curvature drifts became appreciable; therefore, electrons circled around the region of large magnetic field.